2005
DOI: 10.1177/002182860503600107
|View full text |Cite
|
Sign up to set email alerts
|

Jules Janssen's ‘Revolver Photographique’ and its British Derivative, ‘the Janssen Slide’

Abstract: The first practical device for sequential photography, invented to record the transit of Venus in 1874, was later recognized as the precursor of the movie camera. At least technically much more successful than is usually thought, Janssen's 'revolver photographique' was only grudgingly tolerated by the French authorities in 1874, but it was widely adopted in modified form by the British; the story is told in the light of the holdings of the Royal Observatory Greenwich manuscripts, now in Cambridge University Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Unfortunately, the widely-reproduced plate of his observations is not of the actual transit but rather of a previous test (Fig. 7), as shown by Launay & Hingley (2005). They showed that it was first published in 1891 and then reproduced in Janssen's Oeuvres Scientifiques of 1929.…”
Section: Historymentioning
confidence: 95%
See 1 more Smart Citation
“…Unfortunately, the widely-reproduced plate of his observations is not of the actual transit but rather of a previous test (Fig. 7), as shown by Launay & Hingley (2005). They showed that it was first published in 1891 and then reproduced in Janssen's Oeuvres Scientifiques of 1929.…”
Section: Historymentioning
confidence: 95%
“…16. Reports from observers all over the world indicate that the black-drop effect was less prominent than had been expected, though such comments had also appeared in reports of the 19th-century transits (Launay & Hingley 2005). Since prior knowledge showed that the black-drop effect was not intrinsic to Venus but was rather a combination of instrumental effects and effects to some degree in the atmospheres of Earth, Venus, and Sun, it is no surprise that the better telescopes we have now, since the time of Captain Cook, provide cleaner images and potentially less black drop.…”
mentioning
confidence: 98%
“…So, it is most surprising that there is so little memory remaining from Bénard's cinematographic work. The chronophotography allowed no more than an analysis of fleeting dynamic phenomena at a more leisurely pace, just like Jules Janssen's had wished to do when he invented the photographic revolver that is the ancestor of cinema (Canales 2002(Canales & 2006Launay & Hingley 2005). The cinematograph, on the other hand, was designed to recreate the studied phenomenon: "giving the observer the faculty of seeing again the scene that he studies as many times as necessary" (Anonymous 1909, p. 682).…”
Section: In 1973 a Conference On Instability And Dissipative Structurmentioning
confidence: 99%
“…Janssen was elected in 1873 at the French Academy of Sciences. He was the inventor of the photographic revolver (Launay & Hingley, 2005) to record the Venus transit observed in Japan in 1874, and more generally to produce motion pictures of dynamic events. The revolver may be considered as a remote ancestor of the cinematograph.…”
mentioning
confidence: 99%